Analysis of the Determinants of Credit Risk: Empirical Evidence from The European Union Banking Industry - CHEN, YOURAN (2018)
Credit risk can be described as one of the major risks facing the banking industry. It is the possibility that a bank borrower or counterparty fails to fulfil its obligations under agreed terms. In general, credit risk can be measured by the bank’s non-performing loans and capital adequacy ratio on the balance sheet, which are influenced by macroeconomic conditions, counterparty characteristics and bank-specific factors. This dissertation empirically analyses the determinants of credit risk based on the European Union (EU) banking system during a2011-2018. The reason for choosing 2011 to 2018 is that this period includes periods of rapid economic growth and the downturn of economic growth. In terms of methodology, this dissertation focuses on macroeconomic determinants and microeconomic determinants of credit risk, using static panel data methods to examine the relationship between banking credit risk and these economic determinants. According to the empirical results, it suggests that unemployment rate, interest rate, loan loss provision and regulatory capital are significantly positively related to non-performing loans. And inflation rate, bank size and return on assets have significant negative relationship with non-performing loans. In terms of capital adequacy ratio, it is significantly negatively influenced by GDP growth, interest rate and exchange rate. In addition, inflation rate, loan loss provision and regulatory capital have significant negative relationship with capital adequacy ratio.